(untitled) (Revista Lusófona de Educação, 2024)
The democratic participation of students in school governance has been provided for since the Constitution of the Portuguese Republic (1976) through participation in collegiate school management bodies, which continues to this day in the representation of students, with voting rights, on the General Council (DL75/2008), heard by the Pedagogical Council and through the Students’ Association. Nevertheless, paradoxical times and contradictory logics persist in schools, between neoliberal, elitist and individualistic discourses and other participatory practices and experiences with autonomy and freedom (Apple & Beane, 2000; Biesta, 2016; Sant, 2019). Within this framework, we asked ourselves “Is school management democratic for students?” and sought to identify and understand experiences of autonomy and democratic practices in decision-making about school management in the voice of students. From a partial snapshot of the current study and the responses to a questionnaire survey of secondary school students, we can see that they recognise spaces to participate, be heard and make decisions in management bodies (general council, pedagogical council and meeting with the headmaster). Still, they value other spaces for direct participation, through delegates and in the class group. There are new challenges for students in democratic management, which result from the centralisation of powers in the one-man management body and the exacerbated pressure and demands on school results. Keywords: educational policy; school autonomy; democratic management; student participation.